2019
DOI: 10.1007/s12550-019-00346-y
|View full text |Cite
|
Sign up to set email alerts
|

Feeding study for the mycotoxin zearalenone in yellow mealworm (Tenebrio molitor) larvae—investigation of biological impact and metabolic conversion

Abstract: Edible insects as additional food and/or feed source may represent one important component to solve the problem of food security for a growing human population. Especially for covering the rising demand for protein of animal origin, seven insect species currently allowed as feed constituents in the European Union are gaining more interest. However, before considering insects such as yellow mealworm larvae ( Tenebrio molitor ) as suitable for, e.g. human consumption, the possible presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 58 publications
5
42
2
Order By: Relevance
“…However, β-ZEL and its sulfate as well as ZEL-glucosides were not detected in the fermented tempeh-like product. This result is in line with previous results from liquid culture experiments [31] and expecially the absence of β-ZEL shows that the metabolism of the investigated fungi is significantly different from other species such as mammals or insects always forming α-ZEL along with β-ZEL [36,39]. Moreover, all tempeh-like products were also screened for presence of diglucosidic and disulfated derivatives.…”
Section: Resultssupporting
confidence: 89%
“…However, β-ZEL and its sulfate as well as ZEL-glucosides were not detected in the fermented tempeh-like product. This result is in line with previous results from liquid culture experiments [31] and expecially the absence of β-ZEL shows that the metabolism of the investigated fungi is significantly different from other species such as mammals or insects always forming α-ZEL along with β-ZEL [36,39]. Moreover, all tempeh-like products were also screened for presence of diglucosidic and disulfated derivatives.…”
Section: Resultssupporting
confidence: 89%
“…The lack of ZEN uptake in Lesser Mealworm is in agreement with the literature [19], while the possible transferal of DON and FB1 in LM larvae grown on naturally incurred substrates, was observed in this study for the first time.…”
Section: Discussionsupporting
confidence: 93%
“…However, despite a growing interest, only few papers have addressed the possible uptake and biotransformation of mycotoxins in insects so far [17,18,19,20,21,22]. Although information on the possible biotransformation and/or excretion mechanisms are still scattered, all the studies performed to date consistently demonstrated that parent mycotoxins are not bioaccumulated by insects grown in contaminated substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that insects-if kept on rotten and/or mouldy substrates-may render hazardous metabolites harmless via their own metabolism or largely excrete them, especially mycotoxins, such as zearalenone or type B trichothecenes (Niermans et al 2019;Ochoa Sanabria et al 2019;Van Broekhoven et al 2017). However, as shown for zearalenone, metabolism in T. molitor may also result in the formation of compounds of higher toxicity, such as αzearalenol (Niermans et al 2019). Based on these studies, it could be possible to obtain a safe product for further use for food or feed through insects reared on material no longer suitable for animal or human consumption.…”
Section: Introductionmentioning
confidence: 99%